Russian Adaptation of the PhoPhiKat Questionnaire of Gelotophobia, Gelotophilia and Katagelasticism in Adolescents - Stefanenko E. A.; Ivanova E.M; Enikolopov S. N. (Moscow State University of Psychology and Education, 2017)
The article describes results of Russian adaptation of the PhoPhiKat, a questionnaire to measure gelotophobia, gelotophilia, and katagelasticism, on 392 Russian adolescents. The results confirm three-factor structure of the questionnaire and demonstrate reliability and construct validity of the scales.Most of the items have loadings to the intended factors, but a number of items have worse psychometrical properties. Therefore, the reduced version of the method, Phophikat<30>, adapted earlier on adults, is recommended for practical usage. The article also presents the analysis of gelotophobia, gelotophilia and katagelasticism expression, their correlations with age, sex and humour styles in adolescents from Russia, compared to Denmark and Switzerland, and Russian adults.